Victims of Compromise - J. Gertrud Tönsing (African Journal of Gender and Religion (AJGR))
This essay gives a brief overview of the authorship debate of Colossians and Ephesians, and argues that the letters, authored mainly by his co-workers, were written as an attempt to compromise between Paul’s controversial views and the congregations of Asia Minor. The household code of Colossians is analysed as a possible accompaniment to the letter to Philemon and the sending back of Onesimus, using the Pauline passage on submission in Ro- mans 13 as a basis, complemented by known Graeco-Roman traditions on the household. Slaves, and not women were the primary addressees of this probably earliest Christian household code, but undoubtedly then the status of women became an issue of contention. The essay argues that Ephesians was written as a modification to the Colossians letter, which had left out key controversial Pauline terms. The letter to the Ephesians pleads for unity, re- introduces Pauline terms in formulations acceptable to the mainstream con- gregations, and carefully formulates a position on women in the household, which was to become dominant in the early church. It is argued that the household codes were regarded as a necessary compromise at the time but were not initially intended to suppress the participation and leadership of women. However, the controversy heated up and became more bitter, leading to the later Pastoral Letters and other early Christian writings, completely suppressing women’s leadership in the church.